ACESSO ESPECIAL AO ENSINO SUPERIOR DE FILHOS DE EX-COMBATENTES – ANGOLA - Alfredo, Daguberto Daniel Gamba (2019)
The present work is part of the special access of the children of the former combatants and veterans of the Homeland in Angola, which reflects on the established strategy of the Angolan state in order to help and contribute to those who fought for the freedom of the Angolan people in a critical moment in which the country lived. In fact, with the elaboration of it, we try precisely to understand the impact that this integration causes as well as the benefits, since training is one of the most crucial phases of life for any person, as it tends to contribute, too , in the awareness of these future professionals, bringing them together with the nature of the labor activity, competences, responsibilities, among others, aiming at not only assimilating the didactic, technical, intellectual and technological dimension, but also in its social role as a hegemonic factor the country's educational system and socio-economic development and the stability of their families.